DINAMIKA ISLAMISASI DI NUSANTARA: ANALISIS KAJIAN PUSTAKA ATAS PROSES, TOKOH, DAN AKULTURASI BUDAYA LOKAL - Shapiah, Shapiah (CV. Adiba Aisha Amira, 2025)
This study discusses the dynamics of Islamisation in the Indonesian archipelago through a literature review of the process, the role of key figures, and models of cultural acculturation. Islamisation in the Indonesian archipelago took place gradually through various channels, such as trade, education, politics, and the arts, each of which exhibited different characteristics in each region. The central role of key figures, such as saints, scholars, and sultans, was crucial in integrating Islamic teachings into local social and cultural structures, thereby accelerating the acceptance of Islam among the people. Adaptive acculturation strategies enabled the harmonisation of Islamic values with pre-Islamic traditions, resulting in a distinctive, moderate, and inclusive form of Islam. These findings confirm that the Islamisation process in the Nusantara region not only brought about religious changes but also shaped the cultural and social identity of Indonesian society to this day.